The Effect of Dynamic Capability, Strategic Innovation, and Market Orientation on Competitive Advantage of MSMEs in Culinary Sector - Novianty Djafri; Noorhani Dyani Laksmi; I Ketut Damana; Bambang Suharto (Journal Management & Economics Review (JUMPER), 2026)
This study examines the effect of dynamic capability, strategic innovation, and market orientation on competitive advantage among Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector. In an increasingly dynamic and competitive business environment, culinary MSMEs must develop adaptive and market-driven strategies to sustain superior performance. Drawing upon dynamic capability theory and market orientation perspectives, this research proposes an integrated framework to explain how internal capabilities and external market responsiveness contribute to competitive advantage. A quantitative explanatory research design was employed, using survey data collected from 210 culinary MSME owners and managers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that dynamic capability, strategic innovation, and market orientation each have a positive and significant effect on competitive advantage. Strategic innovation emerges as the strongest direct predictor of competitive advantage. Furthermore, strategic innovation partially mediates the relationship between dynamic capability and competitive advantage, while market orientation significantly moderates the relationship between dynamic capability and strategic innovation. The model explains 67.2% of the variance in competitive advantage, indicating substantial explanatory power. These findings suggest that sustainable competitiveness in culinary MSMEs is achieved through the integration of adaptive capabilities, continuous innovation, and strong market responsiveness. The study contributes to strategic management literature by clarifying the interplay among dynamic capability, innovation strategy, and market orientation in enhancing MSME competitiveness, while also offering practical implications for entrepreneurs and policymakers.